SIMULASI PSIKOLOGIS NOVEL HANYA NESTAPA - Lestari, Ni Wayan Ita (Humanis, 2013)
Freud proposed that the human’s psychological takes place mostly in the level of unconsciousness and dream is the form of the realization of a desire. In this study, the novel of Hanya Nestapa was analyzed since it revealed the psychological of the characters in the story when they experienced bom Bali. There are two problems discussed in this study such as the structural and the psychological in the novel. The related theory used in this study are the theory of psychoanalysis and the theory of dream interpretation which are further used to find out the aims of the study.
Keywords: novel, structure, psychology